Pengaruh Usaha Preventif Untuk Mengurangi Resiko Lakalantas Ditinjau Dari Pemahaman Pelajar SMP dan SMA di Kabupaten Ngawi - Wibiatmojo, Abram, Nurul Hidayati, PhD, Drs. H. Gotot Slamet, M.T (2016)
Traffic accident is an incident in which the vehicle collided with another vehicle and cause someone injury and loss. One of the causes of traffic accidents is the human factor, including in Ngawi. In Ngawi, most accident victims on the highway are students, which is about 70% of the total casualties. This study aims to determine the characteristics of traffic accidents in Ngawi, knowing students' understanding of traffic rules before and after an attempt at riding safety training and education about traffic rules. Traffic accidents were observed characteristics include: type of vehicle, age, and cause of traffic accidents. This study involved 300 respondents, which provides answers to a questionnaire containing 35 items of questions to understand traffic signs, 7 items of road signs, 15 items of riding procedure, and 10 items of safety riding. The results showed the majority of victims of traffic accidents are motorcyclists aged around 16-30 years. Most of the traffic accidents caused by not knowing traffic signs and road markings. Results of the test data before any attempt to gain an understanding of traffic signs, road markings, the procedure of driving and riding safety respectively, are: 9%, 17%, 9% and 10% of respondents had an average of correct answers as many as 16, 3, 6 and 5 questions. After an effort, the percentage and the average number of correct answers increased. Same as without an efforts, successive values obtained are: 15%, 31%, 22%, and 38% of respondents had an average of correct answers as many as 33, 7, 14 and 10 questions.